An epistemology in order to understand Andean national identities - Pardo Moreno, Pablo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The adjustment between state and nation in Latin America has seen complications since the founding of its republics. The plurality of subjectivities, material realities, and gaps, added to the current unsatisfied demands and a weak institutionality, have influenced the national constructions to have had a populist component in different refounding attempts. In the Andean countries, this component is expressed from sociopolitical conditions prior to performative national identities and the presence of personalistic leadership. Part of the studies on national identities in these countries focused on the analysis of their leadership and discourses. Others chose to focus on the processes or conditions of possibility that favor the irruption of these identities. The objective of the work is to provide an epistemological basis that emerges from the compatibility between the previous explanatory approaches to national identities.